The clinical pastoral education course - Pangrazzi, Arnaldo (Medicina e Morale, 1990)
Courses of Clinical Pastoral Education (CPE) were introduced in Italy a few years ago, afler the experience of the United States and some European countries. These courses aim to give priests, monks and nuns, deacons, theology students, and health and voluntary workers a deeper understanding of the sick person. This favours the development of pastoral methods based on communication and authentic help. It facilitates the process of theological study with pastoral practics and promotes team work wilh experts from other disciplines. In the light of his own experience, the author examines the method used to supply this kind of preparation. On one hand there is written informalion by the student and on the other hand there is a series of interviews with a supervisor. Moreover the CPE uses lhe group dynamic to offer the student reciprocal help and understanding in order to bring him closer to the sick person.